Synthesis of (Bi1−xSbx)2S3 solid solutions via thermal decomposition of bismuth and antimony piperidinedithiocarbamates. Issue 28 (21st May 2019) - Kun, Walter N.; McNaughter, Paul D.; Nyamen, Linda D.; Spencer, Ben F.; O'Brien, Paul; Ndifon, Peter T.; Revaprasadu, Neerish
Abstract : A full range of (Bi1− x Sb x )2 S3 solid solutions from bismuth and antimony piperidine dithiocarbamate complexes is reported. Abstract : The synthesis of the complete range of (Bi1− x Sb x )2 S3 solid solutions, where 0 ≤ x ≤ 1, by the variation of the mole ratio of bismuth and antimony piperidine dithiocarbamate complexes is reported. There was a near linear expansion of a and c lattice parameters as the mole ratio of the antimony precursor was increased. The composition of the particles directionally followed the amount of precursor ratio used. When the composition of particles was compared to cell parameters, a slight deviation from Vegard's law was observed with a corresponding contraction of the b parameter and an approximately 3.5% reduction of the lattice volume. The nanorods obtained showed aspect ratios that depend on the composition of the material. The Bi and Sb rich materials had high aspect ratios of 16.58 and 16.58 respectively with a minimum aspect ratio of 2.58 observed for x = 0.50.